CONDUCTING JOB ANALYSIS IN KSP TRI GUNA MULYA TO IMPROVE EMPLOYEE PERFORMANCE - Widiarini, I Gusti Ayu Diah; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2018)
Abstract. As  one  of  the  cooperative that  can  support the  financial inclusion, KSP  Tri  GunaMulya should  have  a  good management team in managing the financial and sustainability of the cooperative’s performance. However, the result of interview that had been conducted on employee of KSP Tri GunaMulya show that there is less conscientious during work because of mixing job between employee. Therefore, this research is conducted to increase the employee performance in KSP Tri GunaMulya with help them to understand the duties and responsibility that need to be done. This can be done through conducting job analysis, since there is unclear job analysis that could make the employee confused about their duties. The current job that had be done in KSP Tri Guna Mulya was compared with the result of job analysis and it show that there are some positions that have overlapping. With the new job analysis, it could be improve performance and reduce the less conscientious of the employee toward their duties and responsibility. This result may not be able to be used to other cooperative. However, the method are still can be used to design a clear job list for employee.  Keyword:Job Analysis, Job Description, Job Specification, Employee Performance